Measuring the effect of antenatal family planning counseling on the intention for early postpartum family planning among postpartum mothers in Western Kenya - Shisanya, Morris; Kipmerewo, Mary; Morema, Everlyne; Ouma, Collins (Ethiopian Journal of Reproductive Health, 2025)
Introduction: Maternal and Child Health (MCH) care continuum provides a great opportunity for PPFP interventions integration especially antenatal FP counseling. This study measured the effect of antenatal FP counseling on the intention for early PPFP among postpartum mothers in Kisumu County. Methodology: The study compared the effectiveness of different modes of family planning counseling on the intention for early PPFP among postpartum mothers in Kisumu County. It employed ordinal regression analysis to identify predictors of intention and binary logistic regression analysis to assess intention’s predictive power on actual uptake, with statistical significance set at P < 0.05. Results: The mean intention for early PPFP at 3 months postpartum was 6.22 out of a 7-point Likert scale (88.9%) for all the arms. There was a significantly higher mean intention among the participants in the nurses’ arm 6.59 (94.1%) as compared to the CHW’s 6.05 (86.4%) with a mean difference (MD) of 0.54 (P<0.0001). Likewise, nurses’ arm had a significantly higher mean intention (6.59) as compared to the control arm 6.03 (86.1%) (P<0.0001). No difference was demonstrated between the community arm and the control arm (MD=0.02, P=0.986). A further binary logistic regression analysis demonstrated that intention predicted early PPFP uptake (P<0.0001). Conclusion: Mobile-mediated antenatal FP counseling by the nurses was more effective in increasing intention for early PPFP compared to CHW administered and routine FP counselling for the participants in Kisumu County.